Diterpenes and other constituents from Croton draco (Euphorbiaceae) - Murillo, R M (2001)
Croton draco (Euphorbiaceae) from Guadalupe, San José, Costa Rica was collected in July 1992 and phytochemically studied (leaves, seeds, wood, bark, sap and flowers separately). Commonly known compounds such as 1-hydroxyjunenol, p-hydroxybenzaldehyde, p-methoxybenzoic acid, 3,4,5-trimethoxycinnamyl alcohol, the coumarin scopoletin, the nor-terpenoids 9-dehydrovomifoliol and 2,3-dihydrovomifoliol were obtained. Taspine, two aporphinic alkaloids, the diterpenes 9(11)-dehydrokaurenic acid, hardwikiic acid, the corresponding new 12-oxo derivative as well as five clerodanes and a phorbol ester were also isolated. Three clerodanes were not previously described and their NMR spectroscopical data and MS fragmentation patterns are reported.